The Influence of Mutations and the Impact of the Workplace on Employee Performance - Pajriyan, Khoirul; Razak, Ismail; Paramitra, Yuaniko; Loen, Mishelei (Human Capital and Organizations, 2025)
This study aimed to determine and analyze the effect of mutation and work environment on employee performance at PT. Kereta Api Indonesia (Persero) DAOP 1 Jakarta. The technique used for sampling was saturated sampling; respondents in this study were employees of PT. Kereta Api Indonesia (Persero) DAOP 1 Jakarta. The primary data used in this study was obtained through the distribution of questionnaires to PT employees. Kereta Api Indonesia (Persero) DAOP 1 Jakarta as respondents. The study's results showed that mutations affected employee performance, and the work environment had a positive and significant effect on employee performance. The managerial implication is that effective management of mutations and the work environment will improve individual performance and strengthen the performance of the team and the organization as a whole. In this case, a proactive manager will create a productive work environment that supports employee growth and development.